2021
DOI: 10.1038/s41598-021-92287-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of venous thromboembolism with machine learning techniques in young-middle-aged inpatients

Abstract: Accumulating studies appear to suggest that the risk factors for venous thromboembolism (VTE) among young-middle-aged inpatients are different from those among elderly people. Therefore, the current prediction models for VTE are not applicable to young-middle-aged inpatients. The aim of this study was to develop and externally validate a new prediction model for young-middle-aged people using machine learning methods. The clinical data sets linked with 167 inpatients with deep venous thrombosis (DVT) and/or pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The authors in [27] reported an automatic diagnosis model by using effective ML to predict the important risk factors of VTE collecting patient data of the medical ward at King Chulalongkorn Memorial Hospital from Thailand. Other efforts are being dedicated for the prediction of VTE with ML techniques in young and middle-aged inpatients; for example, [28] develop VTE risk classifiers using models based on multi-kernel learning and random optimization [29]. However, a drawback is that these systems are expensive, big, heavy, and have moderate energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [27] reported an automatic diagnosis model by using effective ML to predict the important risk factors of VTE collecting patient data of the medical ward at King Chulalongkorn Memorial Hospital from Thailand. Other efforts are being dedicated for the prediction of VTE with ML techniques in young and middle-aged inpatients; for example, [28] develop VTE risk classifiers using models based on multi-kernel learning and random optimization [29]. However, a drawback is that these systems are expensive, big, heavy, and have moderate energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that SVM, RF, and XGBoost are the most efficient ML algorithms for classification problems of VTE prediction, respectively. 18 , 19 , 20 Additionally, they are classic and representative algorithms based on different machine learning methods. Therefore, we assumed that the three MLs were effective analytical methods for predicting VTE risk among hospitalized cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Support vector machine (SVM), random forest (RF), and extreme gradient boosting (XGBoost) are the most widely used ML algorithms for VTE prediction. Some studies have shown that SVM, RF, and XGBoost are the most efficient ML algorithms for classification problems of VTE prediction, respectively [18][19][20] . Additionally, they are classic and representative algorithms based on different machine-learning methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These methods would require time and high costto diagnose hundreds of patients. Machine learning and data science currently gave great support tomedical science that many predictive models were able to predict disease outcomes with high accuracy [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Machine learning-based detection of lymphedema currently assists doctors and patients in realtime monitoring lymphedema [14,15].…”
Section: Introductionmentioning
confidence: 99%